Fields of play in modern drama - Whitaker, Thomas R. (Princeton legacy library., 1977)
Starting from the assumption that all theater is at least implicitly participatory, Professor Whitaker approaches thirteen plays, from Ibsen's Rosmersholm to Beckett's Endgame and Stoppard's Rosencrantz and Guildenstern Are Dead. He asks the reader to commit himself to a variety of points of view-those of witnesses, actors, directors, and characters-as a series of ""critical fictions"" lead him toward the experience of each play in performance. The author supplies detailed readings of the plays in various modes. The styles of the chapters vary according to the issues dominant in the plays d